Knowledge Enhancement Through Field Learning : Development Jatijejer Village Into The First Atsiri Village in East Java, Indonesia: Peningkatan Pengetahuan Melalui Pembelajaran Lapangan : Transformasi Jatijejer Menjadi Desa Atsiri Pertama di Jawa Timur - Gondokesumo, Marisca Evalina; Azminah, Azminah; Ardiansyahmiraja, Bobby; Suryaningsih, Dwie Retna (Universitas Lancang Kuning, 2025)
Jatijejer Village located in Trawas Subdistrict, Mojokerto, East Java, has significant potential in agriculture due to its fertile soil but this potential has not been fully optimized. The main crops widely cultivated there are lemongrass (Cymbopogon citratus (DC.) Stapf) and citronella (Cymbopogon nardus (L.) Rendle), which can be processed into essential oils with high economic value and various other benefits. The initial effort in developing Jatijejer Village into the first Atsiri Village in East Java is field learning, which provides a comprehensive overview of the target goals. Hortus Medicus and Rumah Atsiri Indonesia in Tawangmangu, Central Java, were chosen due to their experience in cultivating and processing aromatic plants and producing essential oils. This field learning involved 30 participants, including village officials, representatives of farmer groups, PKK, BUMDES of Jatijejer Village, and community service teams from the University of Surabaya and Wijaya Kusuma University Surabaya. Each participant completed pretests and posttests to measure knowledge improvement after the field learning. The results showed an increase in participants' knowledge, with an average pretest score of 58% rising to 98% in the posttest. This field learning activity proved effective in enhancing participants' knowledge, supporting the success of the village development program, and optimizing the economic and tourism potential of Jatijejer Village.